2017
DOI: 10.1177/000313481708300317
|View full text |Cite
|
Sign up to set email alerts
|

Evolving Trends and Influencing Factors in Mastectomy Decisions

Abstract: It is known that survival is unaffected by the choice of surgical management for breast cancer (BC) patients. Despite this fact, recent literature reveals that the number of bilateral mastectomies (BMs) in the United States is increasing. In an effort to elucidate potential factors influencing this trend, we investigated socioeconomic and clinicopathologic characteristics of our patient cohort that could have affected a patient's decision between unilateral mastectomy (UM) versus BM. Five-hundred-eight patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
18
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(21 citation statements)
references
References 19 publications
(22 reference statements)
3
18
0
Order By: Relevance
“…This means that patients in the highest SES decile were 63.4% (95% CI; 60.4e66.8%) more likely to undergo IBR than patients in the lowest SES decile. This contributes to previous knowledge from studies which showed the effect of SES on the treatment of breast cancer [12,28,29]. The current study is also in line with a recent Swedish study which showed that age and SES contribute to the likelihood of receiving postmastectomy IBR [30].…”
Section: Discussionsupporting
confidence: 91%
“…This means that patients in the highest SES decile were 63.4% (95% CI; 60.4e66.8%) more likely to undergo IBR than patients in the lowest SES decile. This contributes to previous knowledge from studies which showed the effect of SES on the treatment of breast cancer [12,28,29]. The current study is also in line with a recent Swedish study which showed that age and SES contribute to the likelihood of receiving postmastectomy IBR [30].…”
Section: Discussionsupporting
confidence: 91%
“…The second study examined 2-year satisfaction with scores on the BREAST-Q survey, a validated patient-reported outcome instrument. 2 The authors found greater satisfaction and breast-related quality of life in patients who underwent au-Related articles pages 891 and 901…”
Section: Disclaimermentioning
confidence: 99%
“…The incidence of women with breast cancer who elect to undergo contralateral prophylactic mastectomy is steadily increasing, with preponderance amongst Caucasians, young women, and those with a higher socioeconomic status [1,2]. A study of 496,488 women with unilateral Stage I-III breast cancer, from the Surveillance, Epidemiology, End Results (SEER) Program database demonstrated an increase in contralateral prophylactic mastectomy rates performed for unilateral invasive breast cancer from 3.9% in 2002 to 12.7% in 2012 [3].…”
Section: Introductionmentioning
confidence: 99%
“…Factors that contribute to this decision include patient age, disease stage, previous breast biopsies, genetic predisposition or family history of breast cancer, fear of recurrence, concern with cosmetic symmetry and physician recommendation [1,[5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%